Pengaruh Penambahan Pigmen Warna pada Filamen PLA SUNLU Colors dan SUNLU Natural - Ahmad, Noesanto Dewantoro; Sukamto, Sukamto; Pratama, Bagas Risda (Jurnal Mesin Nusantara, 2024)
3DP technology is experiencing rapid development and is widely used in various fields. PLA material is widely used as a material for making filaments used in 3D printing (3DP). PLA filament in 3DP is widely used because it has many advantages, including biocompatible, biodegradable, and non-toxic. When compared with other filament materials, PLA material is easier and safer to use because the temperature used is relatively lower so it is more energy efficient compared to other filament materials. SUNLU is a well-known manufacturer that provides various types of quality filaments, including PLA Colors and PLA Natural, where each type of SUNLU PLA filament has its characteristics and advantages. The choice of PLA filament type is adjusted to the desired printing needs, including the desired color and visual effect. The use of color pigments in PLA filaments with various color choices is used to produce objects that are more attractive and more flexible in their use in various fields. This experimental research was carried out to determine the effect of adding color pigments to SUNLU PLA Colors and SUNLU PLA Natural 1.75 mm filament samples with predetermined sample manufacturing variables. This research uses the ASTM D638 type V standard tensile test so that the tensile strength value of each sample can be determined and the maximum value from the tensile test can be determined. The results of this research will show a comparison of the tensile strength between SUNLU PLA Colors filament samples and SUNLU PLA Natural 1.75 mm. The tensile test results of the SUNLU PLA Natural sample had a higher value, namely 53.98 MPa, and for the SUNLU PLA Colors Orange and Gray samples, each had a tensile strength value of 46.58 MPa and 46.63 MPa. These results show that adding color pigments to the filament affects the strength of the resulting 3D-printed samples